Qital Dalam Alquran dan Hadis: Tinjauan Historis dan Praksis - Nuryansah, Mohamad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2018)
This paper aims at responding a critical accusation of qital concept in the Qur’an and hadith and providing analyses by using historical and practical approach. It can be argued, then, that the purposes of qital can be explained correctly as directed by both sources. At the very practical of interpretative approach, this study employs the historical, eidetic, and practical criticism. The research argues that qital or war can be applied with some criterias and ethics based on the Qur’an and hadith instruction. These criteria are (1) The nature of qital should be directed into God (fi sabiillah); (2) The qital should be first caused by the war of the enemy, (3) The qital is not permitted in the sacred worship places, (4) It aims to relieve the slander, (5) It is not allowed to sacrifice of other Muslims. The ethics of qital are: (1) It is not permitted to overreach, (2) Moslems must end the war if the enemy are surrender, (3) it is obliged to do based on the regulations and the aggrement, (4) it is not permitted to destroy.